2018
DOI: 10.1111/ijfs.13850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sensory and physical properties of meat and fish derivatives containing grape pomace powders

Abstract: The wine industry produces tons of pomace that, in a circular economy model, should be valorised. The phenols fraction of grape pomace represents a source of food colorants, but also of natural food preservatives. Furthermore, the pomace contains dietary fibre, unsaturated lipids, antioxidants and minerals that have been recognised as wholesome and technologically useful. The main drawback of using grape pomace is represented by its chemical and microbiological instability. Different authors proposed strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
1
27
0
1
Order By: Relevance
“…The cohesiveness of the control samples was generally higher than that of the fibre groups in regard to Spanish sausages. Similar results were found when meat and fish products were enriched with grape pomace [ 26 ]. According to Han and Bertram [ 28 ], the majority of previous studies have shown that a reduction of fat in emulsified meat products leads to a firmer texture due to the presence of more tight connections among the meat particles and a more dense structure caused by the reduction in fat.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The cohesiveness of the control samples was generally higher than that of the fibre groups in regard to Spanish sausages. Similar results were found when meat and fish products were enriched with grape pomace [ 26 ]. According to Han and Bertram [ 28 ], the majority of previous studies have shown that a reduction of fat in emulsified meat products leads to a firmer texture due to the presence of more tight connections among the meat particles and a more dense structure caused by the reduction in fat.…”
Section: Resultssupporting
confidence: 82%
“…Other authors also observed a reduction in b* after the addition of vegetable fibres [ 21 , 24 ]. Mainente et al [ 26 ] revealed that flavonoids are the molecules that are primarily involved in the colour of grape pomace, and it must be considered that the colour of anthocyanins could vary from red to blue depending on the pH value. However, phenols can influence the colour of meat based on their antioxidant activity, there they primarily act on myoglobin [ 27 ] but can also influence lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the products included in this SI cover a broad range: from sugarcane (Fang et al., ), broccoli (Krupa‐Kozak et al., ), meat and fish derivatives (Mainente et al., ), pomegranate (Singh et al., ), grape pomace (Jiménez‐Martínez et al., ) and papaya (Nieto‐Calvache et al., ). Other studies, for example, report noteworthy data related to industrial enzyme production (Taddia et al., ) and selective separation of inhibitory peptides from rainbow trout (Ketnawa et al., ).…”
mentioning
confidence: 99%